Expression of Markers of Hepatocellular Differentiation in Pancreatic Acinar Cell Neoplasms: A Potential Diagnostic Pitfall - Askan, Gokce (Am J Clin Pathol, 2016)
Objectives: Pancreatic acinar cell carcinoma (ACC) is a rare tumor that frequently metastasizes to the liver and may present a diagnostic challenge due to its morphologic similarity to hepatocellular carcinoma. We investigated α-fetoprotein (AFP), hepatocyte paraffin antigen 1 (HepPar 1), glypican 3, arginase 1, and albumin messenger RNA (mRNA) in situ hybridization (ISH) in pancreatic neoplasms with ACC differentiation to assess their diagnostic value. Methods: AFP, HepPar 1, glypican 3, and arginase 1 immunohistochemical staining was performed on 28 ACCs using a tissue microarray. Albumin mRNA ISH was performed on full-faced sections. Results: Fifteen tumors were positive for at least one marker. Glypican 3 was positive in seven of 28, AFP in five 28, and albumin mRNA ISH in five of 20. None expressed arginase 1. Conclusions: Hepatocellular differentiation markers, including albumin mRNA ISH, may be positive in ACC, but arginase 1 appears to be uniformly negative. Thus, its use may improve the accuracy in distinguishing these neoplasms from hepatocellular carcinoma. If ACC diagnosis is considered, acinar differentiation can be reliably demonstrated by trypsin/chymotrypsin.